Technological Pedagogical Content Knowledge (TPACK) sebagai Kerangka Pengetahuan Guru Abad 21 dalam Pembelajaran IPA - Syahidi, Khaerus; Mulia Rasyidi; Muh. Zaini Hasnul Muttaqin; Asrorul Azizi; Tsamarul Hizbi (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2024)
21st century teacher must have knowledge at a time Skills in use various device technology good traditional _ as well as modern for facilitate study and increase results learning. Article this aim for define, explain about measurement, and explain about development Technological Pedagogical Content Knowledge (TPACK). Writing article use method study References from various article reputable international journal _ related with topics discussion. Study results show that, TPACK is wrong something type knowledge new which must controlled teacher for could integrate technology with good in learning, measurement TPACK is activity evaluation level TPACK mastery carried out use TPACK frameworks, and development TPACK is continuation from process measurement which conducted for increase mastery TPACK. TPACK could made as framework work for designing curriculum more teacher education in accordance with era and demands learning Century 21.